Integrasi Sistem Coretax dan PSAK 73 dalam Digitalisasi Bukti Potong PPH Final atas Transaksi Sewa: Studi Kasus pada Perusahaan di Indonesia - Izdihar Shada; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the Coretax information system in the digitalization of withholding tax evidence for final income tax on lease transactions and its linkage with PSAK 73 implementation in companies. The research focuses on the use of unified electronic withholding tax certificates (e-Bupot) through the Coretax system as part of Indonesia’s tax administration digital transformation. A qualitative descriptive approach is applied, using document observation, interviews, and a literature review. The research data are derived from a lease transaction between PT ABC Indonesia and PT QYP, including the lease agreement, invoice, electronic tax invoice, billing code, and unified e-Bupot. The data are analyzed by examining the digital tax reporting workflow, the accuracy of Final Income Tax Article 4 paragraph (2) calculations, and the conformity of lease accounting treatment with PSAK 73. The results indicate that the implementation of Coretax improves efficiency, accuracy, and traceability in lease tax reporting, while also supporting data consistency between tax reporting and financial reporting. Therefore, the integration of Coretax and PSAK 73 plays an important role in strengthening transparency, accountability, and good governance in digital tax administration at the corporate level.